Comparative Study of WSN Routing Protocols in Smart Agriculture Applications (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
The application of smart agriculture based on Wireless Sensor Networks (WSN) has become an important solution in improving the efficiency and sustainability of the agricultural sector through real-time environmental monitoring. However, the limited energy resources of sensor nodes make the selection of routing protocols a crucial factor in determining network performance and lifespan. This study aims to conduct a comparative study of the performance of several WSN routing protocols in smart agriculture applications to determine the most efficient and reliable protocol. This study uses a quantitative simulation-based study method with an experimental approach. Several WSN routing protocols representing cluster-based, chain-based, and threshold-based approaches were tested in identical network scenarios. Performance evaluation was based on the parameters of energy consumption, network lifetime, throughput, packet delivery ratio, and end-to-end delay. Simulation results showed that the cluster-based routing protocol had the lowest energy consumption of 45 J, the longest network lifetime of up to 1800 rounds, the highest throughput of 92 kbps, and a packet delivery ratio of 96%.  Chain-based protocols exhibit the highest energy consumption and greatest delay, while threshold-based protocols produce lower throughput due to their condition-based data transmission mechanism. This study found that cluster-based routing protocols are the most optimal solution for smart agriculture applications that require periodic and long-term monitoring. The results of this study emphasize the importance of selecting routing protocols that are suitable for the characteristics of the application, and open up opportunities for further research on the development of adaptive and hybrid WSN routing protocols to improve the efficiency of smart farming systems.
Keywords: Keywords: Wireless Sensor Network, Routing Protocol, Smart Agriculture, Energy Efficiency, Network Lifetime